Changing the coefficient of x to 6 changes the meaning of the expression as 5 is added to 6 times x
Solution:
Given that number 2 in the expression 5 + 2x is called the coefficient of x
We are asked to find what happens when changing the coefficient to 6 changes the meaning of the expression
In the expression,
5 + 2x
This means 5 is added to 2 times x or 5 is added to twice of x
Number 2 is called the coefficient of x
When we change this coefficient to 6, the expression becomes,
5 + 6x
So now the meaning of expression becomes,
5 is added to 6 times x
So changing the coefficient of x changes the meaning of the expression
Answer:
Step-by-step explanation:
k = xy
Putting values of x and y in the equation
k = (5)(-3.5)
= - 17.5
Finding value of x when y = 10
k = xy
- 17.5 = x10
Bringing like terms on one side
- 17.5 - 10 = x
-27.5 = x
The mistake is line 4, she should have divided 42 by 5, not add 5 and 16
G(x) = 2x + 2
g(a + h) - g(a) = 2(a+h) + 2 - (2(a) + 2)
g(a + h) - g(a) = 2a + 2h + 2 - 2a - 2
g(a + h) - g(a) = 2h + 2 - 2
g(a + h) - g(a) = 2h
Your final answer is a. 2h.
Answer: y= - 2/3x+6
Step-by-step explanation:
Just plug in values into this equation (slope intercept form)
y=mx+b
3 is x value
4 is y value
m is the slope which is - 2/3
So after you plug in the values, solve for b ("b" is the y intercept):
4=-2/3(3)+b
4=-2+b
b=6
Then add in the b value into your equation and you will get y= - 2/3x+6